EVALUATION OF INDUCED LABOR USING OXYTOCIN INFUSION IN FULL-TERM PREGNANT WOMEN AT LUC YEN MEDICAL CENTER IN 2025 (Vietnam Journal of Community Medicine, 2026)
Background and Objectives: Induction of labor is essential when spontaneous labor fails, reducing maternal-fetal risks. Intravenous oxytocin is the most common method. This study evaluated outcomes of oxytocin-induced labor and associated factors at Luc Yen Medical Center in 2025.Methods: A prospective case series followed 104 full-term pregnant women receiving oxytocin infusion at the Department of Reproductive and Obstetric Health, Luc Yen Medical Center, from April to October 2025. Success was defined as vaginal delivery (including forceps/vacuum) within 24 hours of starting oxytocin; failure as cesarean conversion due to arrested cervical dilation, fetal distress, non-engagement, or hyperstimulation. Data were analyzed using SPSS 16.0 with χ² tests and logistic regression to identify associated factors.Results: Mean maternal age was 27.2 ± 4.2 years; 88.5% had intact membranes on admission. The most common indications were weak/infrequent uterine contractions (48.1%), prolonged labor (37.5%), and premature rupture of membranes (14.4%). The mean Bishop score was 6.18 ± 0.13. The success rate was 73.1%. Among 26.9% failures, 50% were due to arrested cervical dilation, 35.7% to fetal distress, and 14.3% to non-engagement. All newborns had Apgar scores ≥ 7 at minutes 1 and 5; no severe maternal complications (uterine rupture, severe postpartum hemorrhage, ICU admission) were recorded in the study sample. A Bishop score > 6 was significantly associated with success (p < 0.001).Conclusion: Oxytocin-induced labor at Luc Yen Medical Center achieved a 73.1% success rate, with no notable adverse neonatal outcomes recorded in the study sample.
Keywords: Oxytocin, induced labor, full-term pregnancy.